Training Internal Medicine Residents to Perform Telemedicine Visits: A Novel Skill-Based Curriculum - Sarah Jones; Melissa McNeil; Scott D. Rothenberger; Kwonho Jeong; Tanya Nikiforova (MedEdPORTAL)
Introduction Since the COVID-19 pandemic, internal medicine (IM) residents have provided patient care via telemedicine in their continuity clinics but often without formal training in telemedicine skills. To address this education gap, we developed a two-part curriculum to improve IM residents’ self-perceived competence with outpatient telemedicine skills. Methods From May to August 2020, IM residents participated in a 45-minute interactive case-based, small-group discussion focused on patient triage, virtual physical examination, and telemedicine communication skills. Faculty preceptors directly observed resident telemedicine visits and provided residents with formative feedback using a checklist. Residents completed pre- and postsession surveys assessing self-perceived competence with 15 telemedicine skills. Results A total of 119 residents participated in the case-based session, and most (61%) received direct observation. Among these residents, 51% (61/119) completed both pre- and postsession surveys. After completing the curriculum, residents’ self-perceived competence increased for all skills, with the largest gains in triaging patients to visit types, physical exam adaptation, addressing preventative care, and arranging follow-up (mean 0.5 increase in participant ratings based on 5-point Likert scale; p < .001). Improvement in self-perceived competence was independent of resident level of training and video visit volume. Faculty performing direct observations expressed high levels of confidence in the care delivered. Discussion This easily implemented curriculum combining a case-based discussion with direct observation increased IM residents’ self-perceived competence in telemedicine skills and could be readily adopted in IM residency programs and various specialties to provide trainees with telemedicine skills.